PROMOTING HEALTHY AGING OF WORLD TRADE CENTER RESPONDERS. (20th December 2022) - Ornstein, Katherine; Ko, Fred
Abstract: By 2030 the majority of World Trade Center (WTC) rescue and recovery workers (general responders) will be aged 65 and over and at risk for age-related conditions and consequences. Despite the US government's commitment to support WTC responders who have exposure-related health conditions (e.g., cancers, PTSD), little research to date has focused on age-related issues in this population. Because WTC responders were exposed to high levels of toxicants and intense psychological trauma in the emergency response and cleanup following the 2001 WTC disaster—hazards that can accelerate the aging process – they are likely at increased risk for premature aging and associated age-related syndromes (e.g., functional decline, falls). An improved understanding of how aging affects the health of WTC responders is critically important to improving their clinical care, health outcomes, and overall quality of life. In this symposium we will present 3 studies that have shed light on the aging of WTC responders. First, we assess frailty among responder using a frailty phenotype. In the next study we examine the extent of polypharmacy among WTC responders and associated factors. Finally, we examine trajectories of frailty in this population over 2 decades of follow up using a validated clinical frailty index. This work represents the first examination of frailty and aging among WTC responders and will be an area of growing research as the population ages.